Novel tubulin-targeted cell penetrating antimitotic octapeptide. Issue 85 (7th October 2016) - Bhunia, Debmalya; Mohapatra, Saswat; Kurkute, Prashant; Ghosh, Subhajit; Jana, Batakrishna; Mondal, Prasenjit; Saha, Abhijit; Das, Gaurav; Ghosh, Surajit
Abstract : Here, we have discovered an antimitotic cell penetrating octapeptide containing single Arg amino acid. Abstract : An antimitotic cell penetrating octapeptide containing single Arg amino acid is discovered, which strongly binds with the exchangeable GTP/GDP binding site of tubulin, inhibits tubulin polymerization, reduces kinesin driven microtubule motility, activates apoptotic and mitotic check point proteins, induces apoptotic death and significantly inhibits the multicellular tumor spheroid growth of HeLa cells.